2019
DOI: 10.1016/j.fgb.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and population genetics of cryptococcus neoformans and cryptococcus gattii species complexes in Europe and the mediterranean area

Abstract: A total of 476 European isolates (310 Cryptococcus neoformans var. grubii, 150 C. neoformans var. neoformans, and 16 C. gattii species complex) from both clinical and environmental sources were analyzed by multi-locus sequence typing. Phylogenetic and population genetic analyses were performed. Sequence analysis identified 74 sequence types among C. neoformans var. neoformans (VNIV), 65 among C. neoformans var. grubii (56 VNI, 8 VNII, 1 VNB), and 5 among the C. gattii species complex (4 VGI and 1 VGIV) isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 52 publications
6
34
0
1
Order By: Relevance
“…Our findings is also similar to what has been reported for Vietnam (83.7%) [ 47 ] and Laos (25%) [ 53 ]. Three other common genotypes—namely, ST2/VNI (13.2%), ST63/VNI (9.8%), and ST40/VNII (9.8%)—were reported in Asia, Africa, Europe, and the United States [ 4 , 10 , 11 , 23 , 54 ]. Interestingly, the most common genotype among the environmental isolates, ST4/VNI (25%), was also the most common (32.6%) sequence type isolated from HIV patients outside of the East Asian countries [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings is also similar to what has been reported for Vietnam (83.7%) [ 47 ] and Laos (25%) [ 53 ]. Three other common genotypes—namely, ST2/VNI (13.2%), ST63/VNI (9.8%), and ST40/VNII (9.8%)—were reported in Asia, Africa, Europe, and the United States [ 4 , 10 , 11 , 23 , 54 ]. Interestingly, the most common genotype among the environmental isolates, ST4/VNI (25%), was also the most common (32.6%) sequence type isolated from HIV patients outside of the East Asian countries [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by molecular typing of the fungal isolate which showed it belonged to genotype ST156. This genotype is the most common C. gattii VGI genotype present in Europe [16] and in Italy and was previously identified in Apulia region from Eucalyptus and olive tree samples, and from a series of samples collected in the cages of exotic animals living in a zoo [17]. The only clinical isolate belonging to this genotype was responsible of disseminated cryptococcosis in an HIV patient living in Bari, in the same Italian region [10] (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…Comparison with MLST profiles of global isolates (Fig. 2) showed that the C. gattii VGI isolate here described was identical to several strains recovered from clinical and environmental sources in southern Italy and Spain [16] and was included in an endemic European cluster.…”
Section: Case Reportmentioning
confidence: 64%
“…4). Few population level genetic analyses are available for non-model fungal species, with most of the literature focusing on species of public interest such as phytopathogens (Benne tt et al 2019), human pathogens (Cogliati et al 2019), insect pathogens (Tsui et al 2019), and mycorrhiza (Savary et al 2018). As a result, comparisons are difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%